Cultural Diversity and Identity Building for the European Union - Berkes, Lilla (Federalism as the Future of the Diverse EU?, 2025)
The study aims to formulate a thought experiment on how loyalty and attachment to the state can be created in a (future) federally structured Europe. At the core of the paper is the premise that the European Union is a culturally diverse entity, with different cultural units (dominant cultures, minority cultures, indigenous peoples, immigrants), all having different and sometimes not necessarily compatible needs. However, for the European Union to be able to function as a state (under any system) in the long term, these needs and interests must be balanced, and thus a European identity and, through it, a sense of attachment and loyalty to the European Union can be created. By all means, the diversity of the European Union is not only cultural, and it is not only these needs that need to be balanced in order to be able to function effectively. However, these cultural factors play a prominent role in the identity-based attachment necessary for harmonious coexistence. It is through this attachment, this bond, this identification, that a solid unity can be created, while without this, the individual components of the unit potentially become more difficult to hold together. To examine this question, the study reviews the role of culture within society and in the state, the European Union’s cultural diversity, its connection to social peace, the connection between culture and identity, how identity can lead to loyalty and how a common European identity can be created in order to achieve this loyalty and through this, stability. Keywords: European Union, diversity, cultural pluralism, identity-building, federalism, loyalty, cultural integration.